Law and the citizen - Sarat, Austin (Studies in law, politics, and society ;, 2020)
This volume of Studies in Law, Politics, and Society brings together an international and interdisciplinary array of scholars to explore issues around citizenship and the law. Topics covered include the constitutive nature of citizenship laws and the often complex and unsettled evolutionary journeys such laws take, how undocumented migrants in the United States have coped with being 'unlawful', the close connection between immigration enforcement and citizenship rights in the United States, a sociological and historical reconstruction of the emergence of citizenship as a source of legitimacy for political institutions, and a study of the expressive components of humanitarian activism in the context of immigration enforcement on the border between the United States and Mexico. Through its valuable contribution to our understanding of the relationship between law and citizenship, this volume is essential reading for legal scholars worldwide.